2014
DOI: 10.1111/jpy.12164
|View full text |Cite
|
Sign up to set email alerts
|

Curvature in models of the photosynthesis‐irradiance response

Abstract: An equation for the rate of photosynthesis as a function of irradiance introduced by T. T. Bannister included an empirical parameter b to account for observed variations in curvature between the initial slope and the maximum rate of photosynthesis. Yet researchers have generally favored equations with fixed curvature, possibly because b was viewed as having no physiological meaning. We developed an analytic photosynthesis-irradiance equation relating variations in curvature to changes in the degree of connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 61 publications
(142 reference statements)
1
22
0
Order By: Relevance
“…This is an important result because it shows that light limited photosynthesis is not significantly affected by temperature in polar species. These results must be interpreted with caution because data are scarce, protocols are numerous (i.e., different light sources) and values of α * are estimated by different models, which can lead to significant differences (Frenette ; Jones et al ).…”
Section: Resultsmentioning
confidence: 98%
“…This is an important result because it shows that light limited photosynthesis is not significantly affected by temperature in polar species. These results must be interpreted with caution because data are scarce, protocols are numerous (i.e., different light sources) and values of α * are estimated by different models, which can lead to significant differences (Frenette ; Jones et al ).…”
Section: Resultsmentioning
confidence: 98%
“…The Webb equation is ubiquitous in the literature, probably because it is mathematically convenient and generally fits observations well. Jassby and Platt (1976) found that their hyperbolic tangent equation provided the best overall fit to close to 200 observed curves in a comparison of various equations (Jassby and Platt 1976;Jones et al 2014). Nevertheless, recent studies performed by Jones et al (2014) recommend that Bannister's model (Bannister 1979) is the most appropriate of existing P-I curve equations.…”
Section: Differences Between Photosynthesis Versus Irradiance Modelsmentioning
confidence: 98%
“…Jassby and Platt (1976) found that their hyperbolic tangent equation provided the best overall fit to close to 200 observed curves in a comparison of various equations (Jassby and Platt 1976;Jones et al 2014). Nevertheless, recent studies performed by Jones et al (2014) recommend that Bannister's model (Bannister 1979) is the most appropriate of existing P-I curve equations. This single model with variable curvature could solve the problem of P-I models with fixed curvatures that although they fit observations well they are not always comparable (Frenette et al 1993).…”
Section: Differences Between Photosynthesis Versus Irradiance Modelsmentioning
confidence: 98%
See 2 more Smart Citations